Integration of Entrepreneurial Values for Strengthening Students’ Global Competencies in Islamic Schools: A Case Study at SMP Islam Gandusari - Fara Fariha Rodliyana; Agus Eko Sujianto; Sulistyorini (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Islamic schools in Indonesia face the challenge of equipping students not only with religious knowledge but also with globally relevant competencies. Although entrepreneurship education has gained policy attention in Indonesian vocational settings, systematic empirical evidence on how Islamic junior secondary schools (SMP) integrate entrepreneurial values across multiple educational dimensions to develop students’ global competencies remains limited. This study investigates how entrepreneurial values are integrated at SMP Islam Gandusari and how this integration shapes students’ global competencies. A qualitative case study design was employed, with data collected through observation (eight sessions across four months, March-June 2024), semi-structured individual interviews with twelve key informants (principal, vice-principal for curriculum, two subject teachers, one Islamic education teacher, one entrepreneurship coach, and six students), and analysis of institutional documents including the school’s strategic plan, learning tools, and activity reports. Data were analysed through open coding, thematic clustering, and cross-source triangulation. Findings indicate that entrepreneurial values are integrated through four interconnected channels: project-based learning across multiple subjects, productive extracurricular activities (market day, student cooperative, school radio), consistent habituation of school culture (discipline, honesty, responsibility, cooperation), and the internationalisation of Islamic values into entrepreneurial practice. This integration demonstrably develops students’ creativity, self-reliance, communication, collaboration, responsibility, innovation, and decision-making confidence. These findings contribute a contextually grounded model for Islamic school transformation that positions entrepreneurship education as a character-formation and global competence-building strategy rather than an economic activity add-on